ACOMPARATIVE STUDY ON THE TRANSLATION PROCEDURES USED IN THREE INDONESIAN TRANSLATED VERSIONS OF KAHLIL GIBRAN'S THEPROPHET - Dindin Hetmawan, - (2008)
This study is aimed at comparing the translation procedures used in three Indonesian translated versions (Puslaka Jqya, Pustaka Pelajar and Eska Medid) of Kahlil Gibran's The Prvphet. This paper also tries to find out the most common translation procedures used in those translated versions. Besides that, it also describes the strengths and weaknesses ofthe translated versions based on the reviewers' opinions. The design of the study is descriptive-qualitative method. This study investigated and analyzed 42 paragraphs of 166 paragraphs as the subject of the research. Those data researchwere identified to find the translation procedures using the criteria of translation procedures from Newmark, such as literal, shift/transposition, modulation, synonymy, reduction/expansion, cultural equivalent, paraphrase, addition, couplet, and triplet. Then, the analysis supported the data from the reviewers' perspective to check the naturalness aspects and the quality of the translation product. Finally, the researcher found that all of the translators used more than one procedure in their translations. The most common procedure used by the translators is couplet consists of two translation procedures in one sentence. In this kind of poetic translation, it is proper if the translators apply two translation procedures in order to achieve the accurate, clearand natural translation. The reviewers argued that generally, whole translated versions are acceptable in bahasa Indonesia. However, 3 out of 4 reviewers agree to state that the most natural version comes from Pustaka Pelajar publishinghouse.